Perspectivas sobre a soberania em Carl Schmitt, Michel Foucault e Giorgio Agamben - D'Urso, Flavia (2014)
Sovereignty is a concept made shallow as it presents frail theoretical solutions when applied to aspects from reality. The research hereby aims at understanding Giorgio Agamben s diagnosis on sovereignty by going through the core of Carl Schmitt s thinking in his theory of the sovereign power as well as the displacement of such problem in Michel Foucault s writings. Agamben is an intellectual who perused stern philosophical pathways, sovereignty having stood first and foremost for him along the issue of the potentiality of not being. His approach to reality takes place through the motto to prefer not to, from which he glimpses one possibility for putting down one s relationship between wanting and being able to, and between the constituent and constituted powers. And such annihilation is in effect essential for Agamben since his concept of sovereignty takes into consideration a juridical category not only weakened of its representativeness but most of all originating from an unprecedented biopolitical catastrophe. The path chosen by Agamben for such conclusion is one of a paradigmatic ontology, that is, the axes of understanding for the phenomena which ousted political character from juridical ordinances. The paradigms nuda vita (bare life) and the state of exception mainly constitute the structural elements whose function is to ultimately keep the exception-ridden life of the law. The bottleneck established by sovereignty is undone by a new form-of-life, which means the absolute desecration of a life power over which neither sovereignty nor the law can have control over